Editorial: Avaliação na pós-graduação: critérios em discussão DOI: http://dx.doi.org/10.22169/revint.v13i30.1550 - Both, Ivo José; Almeida, Siderly do Carmo Dahle de (REVISTA INTERSABERES, 2019)
DOI: http://dx.doi.org/10.22169/revint.v13i30.1550